Population genetic structure of Kawakawa (Euthynnus affinis Cantor, 1849) in Malaysian waters based on COI gene - KHALED BINASHIKHBUBKR; AHMAD DWI SETYAWAN; DARLINA MD NAIM (Smujo International, 2023)
Abstract. Binashikhbubkr K, Setyawan AD, Naim DM. 2023. Population genetic structure of Kawakawa (Euthynnus affinis (Cantor, 1849)) in Malaysian waters based on COI gene. Nusantara Bioscience 15: 258-268. Kawakawa (Euthynnus affinis Cantor, 1849) is widely distributed in the subtropical and tropical waters of the Indo-Pacific region. Still, insufficient data about its stock, management, and protection in Malaysia and nearby waters raises concerns about overfishing and depletion. Therefore, to ensure effective and successful management of a species, it is imperative to conduct a molecular-based assessment of the stock structure. The present study investigated the population genetic structure of E. affinis in Malaysian waters using the mtDNA COI gene. Furthermore, the 632 bp segment of the COI region was sequenced in 372 individuals from 19 distinct populations in Malaysian waters. The results revealed that the genetic divergence varied from low to high. The average Haplotype diversity (Hd) and nucleotide diversity (?) were calculated to be 0.5401 and 0.0045, respectively. Examining haplotype distribution unveiled the presence of 22 unique haplotypes within the COI gene of E. affinis. The analysis of the Neighbor Joining (NJ) tree and the Minimum Spanning Network (MSN) revealed the formation of three distinct clades among E. affinis samples. Analysis of Molecular Variance (AMOVA) showed a significant genetic structure among the 19 populations of E. affinis [(FST = 0.5354 (P < 0.05)]. The neutrality test and mismatch distribution analysis indicated that the specimens underwent a period of population expansion. This study is a significant milestone, providing the first comprehensive documentation of the genetic structure of E. affinis in Malaysia.